2019
DOI: 10.3390/nu11020328
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the Level of Trace Elements and Minerals and Folate in Maternal Serum and Amniotic Fluid and Congenital Abnormalities

Abstract: Congenital birth defects may result in a critical condition affecting the baby, including severe fetal/neonatal handicap and mortality. Several studies have shown that genetic, nutritional, and environmental factors may have an impact on fetal development and neonatal health. The relevance of essential and toxic elements on fetal development has not yet been fully investigated, and the results of recent research indicate that these elements may be crucial in the assessment of the risk of malformations in neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…In our previous study, we indicated that some essential and toxic elements were associated with fetal congenital anatomical defects and growth disorders. We found that low concentrations of magnesium and vanadium in amniotic uid and high concentrations of aluminium, cadmium and lead increased the risk of non-genetic birth defects 10 .…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In our previous study, we indicated that some essential and toxic elements were associated with fetal congenital anatomical defects and growth disorders. We found that low concentrations of magnesium and vanadium in amniotic uid and high concentrations of aluminium, cadmium and lead increased the risk of non-genetic birth defects 10 .…”
Section: Introductionmentioning
confidence: 81%
“…Measurement of essential and toxic elements in AF has been described by Markiewicz et al 11 and Kocylowski et al 10 . This method involves the use of inductively coupled plasma mass spectrometry (ICP-MS) technique to assess the levels of Li, Mg, Al, Ca, Cr, Mn, Fe, Co, Ni, Cu, As, Se, Sr and Cd in AF.…”
Section: Element Measurementsmentioning
confidence: 99%
“…It has a protective effect against heart diseases. It decreases the risk of birth of infants with neural tube defects (spina bifida), obstructive urinary tract anomalies, limb deficiencies, orofacial clefts, and congenital hypertrophic pyloric stenosis [74]. After absorption, folic acid is carried as a monoglutamate in the blood and is converted to various compounds in the cell, the most important being the reductase enzyme, tetrahydrofolate (THF).…”
Section: Folic Acid (Fa)mentioning
confidence: 99%
“…The inadequate intake of these micronutrients among young women has been well documented in many developed countries. Low levels of iron and folate have been also found in the daily food rations of pregnant women, which is associated with an increased risk of anemia for the mother, and of neural tube defects for the fetus [1,2]. Iron and folic acid supplementation is therefore recommended as a public health intervention in menstruating and pregnant women, in order to improve their hemoglobin concentrations and iron and folic acid status, and thus reducing the risk of anemia [3].…”
Section: Introductionmentioning
confidence: 99%